2014
DOI: 10.1177/0004867414534476
|View full text |Cite
|
Sign up to set email alerts
|

Psychological outcomes following the Victorian Black Saturday bushfires

Abstract: Objective: We aimed to map the prevalence and predictors of psychological outcomes in affected communities 3-4 years after the Black Saturday bushfires in the state of Victoria, Australia.Methods: Baseline assessment of a longitudinal cohort study in high-, medium-, and low-affected communities in Victoria. Participants included 1017 residents of high-, medium-, and low-affected fire communities. Participants were surveyed by means of a telephone and web-based interview between December 2011 and January 2013. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
171
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(187 citation statements)
references
References 47 publications
8
171
7
1
Order By: Relevance
“…12 The observed low proportion of participants with scores indicating moderate or severe anxiety or depression in the current study is in line with these findings. However, the length of follow-up may have been too short to reflect the full extent of disturbance.…”
Section: Discussionsupporting
confidence: 88%
“…12 The observed low proportion of participants with scores indicating moderate or severe anxiety or depression in the current study is in line with these findings. However, the length of follow-up may have been too short to reflect the full extent of disturbance.…”
Section: Discussionsupporting
confidence: 88%
“…For a small number of participants in this present study who activated the distress and risk assessment and referral protocol, their participation led directly to identifying their individual need for support and connecting them with relevant services. In a separate analysis for this study, it was identified that one-third of those with very severe distress did not consult any health or related professional in the previous month for mental health assistance [21]. Therefore, the inclusion of distress and risk assessment and referral protocols may make an important contribution by identifying the proportion of people within the target population who are experiencing distress after a prolonged period, and reinforcing the availability of local services.…”
Section: Discussionmentioning
confidence: 99%
“…This is graphically highlighted in the 16% response rate obtained by Bryant et al (2014) compared with the 52% response rate obtained using similar methodology in previous studies (McFarlane et al, 1997). Increasingly strict interpretations of privacy legislation controlling medical research is somewhat paradoxical (Loff et al, 2013), particularly in a day and age when individuals' emails are being systematically analysed and used without consent by Internet service providers to target advertising.…”
mentioning
confidence: 80%
“…A population of children exposed to the Ash Wednesday bushfires has now been followed for 28 years (McFarlane and Van Hooff, 2009). Similar to the study of Bryant et al (2014), this study cautioned against viewing the disaster in isolation from the substantial prevalence of traumatic events that occur within the broader Australian community and background psychological morbidity of the disaster victim. Whilst there appeared to be significant long-term educational and socio-economic disadvantage, the only significant difference in relation to psychiatric disorder when compared to a non-exposed comparison group was a greater prevalence of weather phobia in the bushfire-exposed group arising from the extreme wind conditions on the day of the fire.…”
mentioning
confidence: 96%